Theology and Down syndrome: reimagining disability in late modernity - Yong, Amos (Studies in Religion, Theology, and Disability Ser., 2007)
Intro -- Contents -- Preface -- PART I Anticipating Down Syndrome and Disability -- I Introduction Narrating and Imagining Down Syndrome and Disability -- II The Blind, the Deaf, and the Lame Biblical and Historical Trajectories -- PART II Down Syndrome and Disability in the Modern World -- III Medicalizing Down Syndrome Disability in the World of Modern Science -- IV Deconstructing and Reconstructing Disability Late Modern Discourses -- V Disability in Context Feminist, Cultural, and World Religious Perspectives -- PART III Reimagining and Renewing Theology in Late Modernity -- VI Reimagining the Doctrines of Creation, Providence and the Imago Dei Rehabilitating Down Syndrome and Disability -- VII Renewing Ecclesiology Down Syndrome, Disability, and the Community of Those Being Redeemed -- VIII Rethinking Soteriology On Saving Down Syndrome and Disability -- IX Resurrecting Down Syndrome and Disability Heaven and the Healing of the World -- Epilogue -- Notes -- Abbreviations -- References -- Scripture Index -- Index of Authors -- Subject Index.